RESEÑA de: Moreno, César, Mingo, Alicia María de (eds.). Signo, intencionalidad, verdad : estudios de fenomenología. Sevilla : SEFE : Universidad de Sevilla, 2005 - Mingo, Alicia María de (Investigaciones Fenomenológicas, 2007)
_